Giving and Withholding of Information following Genomic Screening: Challenges Identified in a Study of Primary Care Physicians in Estonia - Leitsalu, Liis; Hercher, Laura; Metspalu, Andres (Journal of genetic counseling, 2012)
The use of predictive genomic information to improve medical care remains a contentious topic. However, it is generally agreed that the potential of genomics to improve medicine relies on medical care providers’ ability to effectively communicate and put in context the meaning of test results. As the amount of information available increasingly outstrips providers’ ability to offer qualified judgments on what the information means, consumers inevitably will be faced with test results of uncertain significance, as well as difficult questions about what they do or do not wish to know. Results of this survey of 64 primary care doctors in Estonia suggests that it may be inherently difficult for physicians to withhold genetic information obtained by genome scans or sequencing, even when they believe that having that information is not in the best interests of their patient. The descriptive data suggest introducing genomic medicine through primary care physicians, as proposed by the Estonian Genome Center of the University of Tartu, will require further genetics education as well as a carefully developed set of guidelines for determining where, when and how to use test results.